A liberdade sindical no Brasil e sua importância para a formação da identidade coletiva do movimento sindical - Perrone, Rodrigo (2020)
This dissertation analyzes the importance of freedom of association for modern society and its effects on labor relations. In this context, the present study will address its origin, legal framework, focusing on the various international treaties, in particular the provisions of the Universal Declaration of Human Rights and Conventions n° 87 and 98 of the International Labor Organization, as well as their concept. An overview of the subject is given. Afterwards, it will be discussed the reception of freedom of association and Convention nº 87 in Brazil, through a historical tour, the union system adopted in our country and its consequences, the concepts of oneness, plurality and union unity, thus establishing necessary foundations for the study of freedom of association and its relation with the union democracy and formation of the collective identity of the Brazilian union movement